2010
DOI: 10.1167/iovs.09-4657
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profile of the Developing Mouse Retina

Abstract: Purpose. MicroRNAs (miRNAs) are short, noncoding transcripts that negatively regulate gene expression. They are implicated in diverse cellular processes. The purpose of this study was to obtain a global expression profile of miRNAs in the developing retina and identify differences in miRNA expression between adult rod and cone photoreceptors. Methods. Locked nucleic acid (LNA) microarrays were used to investigate the miRNA transcriptome of the developing mouse retina and brain. Real-time PCR was used to valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 27 publications
11
91
0
Order By: Relevance
“…The developmental increase in expression of miR-9, miR125b, and let-7 family members that we observe in the retinal progenitors confirms and extends earlier analyses of retinal miRNAs (31)(32)(33)(34)(35)(36). The most recent comprehensive microarray and in situ analyses (31,35) show that miR-9, miR-125, and several members of the let-7 family (including let-7a, -b, -c, -d, -e, -f, -g, and -i) are expressed in the retina and increase over the developmental period that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The developmental increase in expression of miR-9, miR125b, and let-7 family members that we observe in the retinal progenitors confirms and extends earlier analyses of retinal miRNAs (31)(32)(33)(34)(35)(36). The most recent comprehensive microarray and in situ analyses (31,35) show that miR-9, miR-125, and several members of the let-7 family (including let-7a, -b, -c, -d, -e, -f, -g, and -i) are expressed in the retina and increase over the developmental period that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…The most recent comprehensive microarray and in situ analyses (31,35) show that miR-9, miR-125, and several members of the let-7 family (including let-7a, -b, -c, -d, -e, -f, -g, and -i) are expressed in the retina and increase over the developmental period that we have analyzed. Moreover, previous in situ localization studies have demonstrated that there is widespread expression of let-7 family members in all retinal layers from E16.5 to adulthood (ref.…”
Section: Discussionmentioning
confidence: 85%
“…Oxygen-induced retinopathy has long served as a useful model for studying pathological angiogenesis (36). Although recent studies reported the expression profiles of many miRNAs in the normal retinas of mice, including miR-329, its targets and function were unknown (44,45). Moreover, only a few miRNAs have been identified to regulate OIR (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Harfe et al, 2005;Harris et al, 2006). Dozens of miRNAs have been detected in the mouse eye, some showing dynamic expression patterns during ocular development (Hackler et al, 2010;Xu et al, 2007). Targeting of Dicer1 in Xenopus embryos revealed its importance for cell-cycle exit, survival and differentiation timing of retinal cells (Decembrini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%